High performance Nb/TiNi nanocomposites produced by packaged accumulative roll bonding. (1st December 2020) - Jiang, Daqiang; Song, Jian; Yang, Hong; Liu, Yinong; Jiang, Xiaohua; Ren, Yang; Yu, Kaiyuan; Cui, Lishan
Abstract: Taking full advantage of intrinsic high strength of nano-reinforcements has been proven difficult in a composite until the concept of strain matching was experimental verified in a nanowire Nb/TiNi in-situ composite, which was obtained via solidifying eutectic Nb/TiNi and subsequent severe wire drawing. However, the volume fraction of the nano-reinforcement was dictated by eutectic reaction, which severely limited the development of high-performance composites. In this paper, the martensitic transformation nanocomposites were successfully acquired with increased volume fraction and changeable morphology of the nano-reinforcement through hot packaged ARB (PARB) and subsequent wire drawing. The nano-reinforcement with lamellar configuration in the composite could exhibit a large lattice strain of ~3.8%, which demonstrated the applicability and effectiveness of the strain matching principle in nano-lamellar composite. The obtained composites show a yield strength over 2.0 GPa and a quasi-linear elastic strain as larger as ~6.5% with adjustable apparent elastic modulus from 30 to 50 GPa.